EPHA1 gene SNPs analysis in population of Ukraine - Gulkovskyi, R.V.; Chernushyn, S.Y.; Kravchenko, S.A.; Bychkova, G.M.; Livshits, L.A. (Вiopolymers and Cell, 2013)
Aim. Analysis the EPHA1 gene G1475A and G1891A alleles distribution in the population of Ukraine, and to study the protein secondary structure as the first step in the investigation of EPHA1 gene involvement in intellectual disability pathogenesis. Methods. Observation group consisted of 300 individuals, including 164 (54.6 %) male and 136 (45.3 %) female individuals. Polymorphic variants were detected using PCR followed by Kpn1 RFLP analysis for G1475A and ARMS PCR analysis for G1891A. Results. The data concerning EPHA1 genotypes and allelic variants distribution were obtained. The low frequency of 1475A allele (0,012) and the absence of 1891A allele (not previously described) were revealed in the population of Ukrainian. Conclusions. Assays for the detection of EPHA1 gene G1475A and G1891A SNPs based on ARMS and restriction analysis were developed and the preliminary data on distribution of G1475A and G1891A polymorphisms in the population of Ukraine were obtained. Мета. Аналіз розподілу алельних варіантів поліморфізмів G1475A і G1891A гена EPHA1 у популяції України та вивчення вторинної структури білка як перший етап визначення ролі гена EPHA1 у патогенезі інтелектуальної недієздатності. Методи. Алельні варіанти SNP для G1475A і G1891A досліджували методами ПЛР- ПДРФ та алель-специфічної ПЛР відповідно. Результати. Отримано дані стосовно розподілу генотипів і алельних варіантів гена EPHA1. Виявлено низьку частоту алеля 1475A (0,012) та відсутність алеля 1891A в популяції України. Висновки. Створено методики детекції замін G1475A і G1891A в гені EPHA1 та проведено попередні дослідження розподілу поліморфізмів G1475A і G1891A у популяції Україні. Цель. Анализ распределения аллельных вариантов полиморфизмов G1475A и G1891A гена EPHA1 в популяции Украины и изучение вторичной структуры белка как первый этап определения роли гена EPHA1 в патогенезе интеллектуальной недееспособности. Методы. Аллельные варианты SNP для G1475A и G1891A исследовали методами ПЦР-ПДРФ и аллель-специфической ПЦР соотетственно. Результаты. Получены данные относительно распределения генотипов и аллельных вариантов гена EPHA1. Выявлена низкая частота аллеля 1475A (0,012) и отсутствие аллеля 1891A в популяции Украины. Выводы. Созданы методики обнаружения замен G1475A и G1891A в гене EPHA1 и проведены предварительные исследования распределения полиморфизмов G1475A и G1891A в популяции Украины.